2021
DOI: 10.1111/his.14461
|View full text |Cite
|
Sign up to set email alerts
|

Some pleomorphic adenomas of the breast share PLAG1 rearrangements with the analogous tumour of the salivary glands

Abstract: Some pleomorphic adenomas of the breast share PLAG1 rearrangements with the analogous tumour of the salivary glands Aims: Pleomorphic adenoma (PA) of the breast, and especially its malignant transformation, is extremely rare and represents a diagnostic pitfall. Molecular alterations in this entity have not been investigated. We aimed to examine the clinicopathological features of our breast PAs and perform molecular analysis. Methods and results: Seven cases of breast PA, including two cases of carcinoma ex PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Recently, it has been demonstrated that some breast PA can harbour PLAG1 rearrangements (comprising a novel fusion gene TRPS1‐PLAG1), similar to the salivary gland counterpart. In breast PA, no HMG2A rearrangements have been detected 51 …”
Section: Tumours With Dual Epithelial and Myoepithelial Cell Differen...mentioning
confidence: 96%
See 3 more Smart Citations
“…Recently, it has been demonstrated that some breast PA can harbour PLAG1 rearrangements (comprising a novel fusion gene TRPS1‐PLAG1), similar to the salivary gland counterpart. In breast PA, no HMG2A rearrangements have been detected 51 …”
Section: Tumours With Dual Epithelial and Myoepithelial Cell Differen...mentioning
confidence: 96%
“…HG‐AdCC (Figure 8) is a very rare condition, characterised by the appearance of a high‐grade type of carcinoma arising in AdCC 51 . At variance with the diagnosis of SB‐AdCC, the high‐grade transformation should be considered when carcinomatous elements with divergent differentiation appear.…”
Section: Tumours With Dual Epithelial and Myoepithelial Cell Differen...mentioning
confidence: 99%
See 2 more Smart Citations
“…Pleomorphic adenomas are benign tumours of the salivary glands found much more commonly in the major salivary glands with incidence of up to ninety percent in the parotid gland, while 10% appear in minor salivary glands [1]. Other reported uncommon sites of pleomorphic adenoma include the submandibular gland [2], nasolacrimal duct [3], lacrimal gland [4], trachea [5], epiglottis [6], and the breast [7]. They are also found incidentally as rigid, unilateral, painless masses, growing gradually [1].…”
Section: Introductionmentioning
confidence: 99%